The New Collective Quantified Goal on Climate Finance (NCQG) - COP29 Negotiation Updates - Chilambe, Pedro; Salfi, Laura; Leonard, Steve; Tesfaye, Lidya; Jalango, Dorcas; Ouedraogo, Issa (2024)
The New Collective Quantified Goal on Climate Finance (NCQG) is a new global climate finance goal that the Conference of the Parties serving as the meeting of the Parties to the Paris Agreement (CMA) shall set from a floor of USD 100 billion per year, prior to 2025. This new goal will be set in the context of meaningful mitigation actions and transparency on implementation, taking into account the needs and priorities of developing countries. Deliberations on setting the new goal aim to strengthen the global response to the threat of climate change in the context of sustainable development and efforts to eradicate poverty, including by making finance flows consistent with a pathway towards low greenhouse gas emissions and climate-resilient development.